Uudistaminen ja yhteistyöverkostot Suomen teollisuudessa: Havaintoja yrityskyselystä - Tuomo Nikulainen; Julia Salmi (The Research Institute of the Finnish Economy (ETLA), 2012)
– The renewal of Finnish manufacturing companies has often been addressed through their innovative activities. But companies do renew themselves in many other ways. This report takes into account, in addition to innovative activities, product and service range, supply and distribution channels, internationalization and marketing. Based on large survey data, the results show that the Finnish manufacturing companies are active in renewing themselves, but independent in their activities. In addressing the co-operation in renewal activities, significant differences can be observed between industries. Few external partners stand out as being important in the renewal processes. The results reveal a broader picture than in previous research efforts on the renewal activities of companies. But, the diversity of these activities makes the incorporation of these dimensions to statistical analysis challenging.
Keywords: O30; O31; O33; 330; Corporate renewal; networks; collaboration